Spatiotemporal characteristics and driving factors of the fractional vegetation coverage in the Ertix River Basin - LIU Yixuan; Alim SAMAT; L.I. Wenbo; Jilili ABUDUWAILI (Regional Sustainability, 2025)
The rapid acceleration of global warming and intensifying human activities have exacerbated the fragility and climate sensitivity of ecosystems worldwide, particularly in arid regions. Vegetation, a key component of ecosystems, is critical in enhancing the ecological environment. The Ertix River Basin (ERB) is a transboundary watershed that spans multiple countries, mostly in arid regions. However, research on the fractional vegetation coverage (FVC) and its driving factors in the ERB remains limited. Investigating the spatiotemporal changes in the FVC and its relationship with various factors in the ERB can offer scientific support for optimizing regional vegetation restoration policies and promoting the coordinated development of human–environment interactions. The Moderate-resolution Imaging Spectroradiometer (MODIS) MYD13Q1 V6 data were obtained via the Google Earth Engine platform, and methods including the pixel dichotomy method, Theil–Sen median trend analysis, and Mann‒Kendall test were employed to examine the spatiotemporal dynamics of the FVC in the ERB from 2003 to 2023, with future trend forecast using the Hurst index. The impacts of natural and socioeconomic factors on the FVC were evaluated through the partial least squares-structural equation model (PLS-SEM). The results indicated that the FVC in the ERB showed a slight degradation trend with an average annual decrease of 0.046% during 2003–2023, with significant changes occurring in 2004, 2010, and 2019. Spatially, 53.380% of the study area was degraded, and the change in the FVC increased gradually from southeast to northwest. The FVC in 63.000% of the study area was highly stable and displayed long-term persistence; and the direct impact of natural factors (path coefficient of 0.617) on the FVC was significantly higher than that of socioeconomic factors (0.167). Among the natural factors, precipitation (0.999) was the most significant. This study reveals the significant impacts of natural and socioeconomic factors on vegetation dynamics in arid regions, and provides a scientific basis for transnational ecological conservation.